The Impact Of Corporate Governance To Financial Performance Of Takaful In Indonesia - Lala Maya Sabrina; Ronald Rulindo (Journal Research of Social Science, Economics, and Management, 2023)
Takaful industry plays an essential role in answering significant issue in the society such as social, economic and environment. The presence of corporate governance become crucial to every Takaful firm in promoting and raising the public trust in one of the Islamic finance ecosystem whom currently to be called as the sleeping giant. Unfortunately, although the regulation has been established by the Financial Services Authority (OJK), certain cases of malpractices and failure of insurance currently rise to the surface. This study contributes to the literature by investigating corporate governance factors that influenced financial performance of Takaful listed in Indonesian Sharia Insurance Association (AASI). Panel Data regression analysis will be used in analyzing the data over the period 2017 – 2021. The data is collected from insurance statistic report published by Financial Services Authority also from annual report and sustainability report of every insurance. Corporate governance variables will be used as independent variables and Return on Asset will be used as a financial performance’s dependent variable. This study provides several corporate governance upon takaful performance from the perspective of a developing country. It also provides an empirical examination of current structures of takaful firms and suggestion to the decision makers and the stakeholders to be adopted in boosting firm performance. This study also gives a recommendation to the policymakers in assessing and reviewing corporate governance policies.